2015
DOI: 10.1123/jsep.2014-0087
|View full text |Cite
|
Sign up to set email alerts
|

Applying Generalizability Theory to Examine the Antecedents of Perceived Coach Support

Abstract: Although social support is integral to the coaching process, there is only a limited understanding of the antecedents of perceived coach support. We applied generalizability theory to examine perceived coach support and its antecedents at perceiver, provider, and relational levels of analysis. Two studies were conducted in which athletes rated the degree to which they identified with a selection of coaches, and the personality, competency, and supportiveness of those coaches. Univariate analyses demonstrated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…As Cohen, Underwood, and Gottlieb (2000) advise, selecting appropriate support strategies from an intervention perspective are not without its challenges. Coussens et al (2015) demonstrated that when athletes perceive specific coaches to be highly agreeable, competent, and individuals with whom they share a common identity, they also perceive these same coaches to be particularly supportive in comparison with other coaches. Future researchers should, therefore, consider completing a baseline support network assessment on the key relationships underpinning the goal of a social support intervention, as this can ensure that interventions are focused on the appropriate antecedents of perceived support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Cohen, Underwood, and Gottlieb (2000) advise, selecting appropriate support strategies from an intervention perspective are not without its challenges. Coussens et al (2015) demonstrated that when athletes perceive specific coaches to be highly agreeable, competent, and individuals with whom they share a common identity, they also perceive these same coaches to be particularly supportive in comparison with other coaches. Future researchers should, therefore, consider completing a baseline support network assessment on the key relationships underpinning the goal of a social support intervention, as this can ensure that interventions are focused on the appropriate antecedents of perceived support.…”
Section: Discussionmentioning
confidence: 99%
“…The findings relating to social identity also point to a key practical implication whereby the cultivation of a common identity can translate effects of perceived available support. These findings suggest that adults (e.g., coaches) who cultivate a common social identity between them and their participants could help to promote participants' perceptions of them as supportive (Coussens et. al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Social support is a complex construct (Bianco & Eklund, 2001), comprised of three key facets [social integration, perceived support, and received support (Lakey, 2010)] and has been recognized as a key factor for the success and well-being of athletes (DeFreese & Smith, 2013;Fletcher & Sarkar, 2012). Since the sample of the study was composed by professional athletes with several years of experience, with a combination of heterogeneous personalities and different personal goals, the impact of Perceived social support could be diminished; also, athletes may systematically disagree in their perceptions of the supportiveness of coaches (Coussens, Rees, & Freeman, 2015;Rees, Freeman, Bell, & Bunney, 2012). Although social support is integral to the coaching process (Coussens et al, 2015), based on the results obtained, we can assume that athletes' prosocial behaviors are not dependable of the Perceived social support provided by the coaches.…”
Section: Discussionmentioning
confidence: 99%
“…Since the sample of the study was composed by professional athletes with several years of experience, with a combination of heterogeneous personalities and different personal goals, the impact of Perceived social support could be diminished; also, athletes may systematically disagree in their perceptions of the supportiveness of coaches (Coussens, Rees, & Freeman, 2015;Rees, Freeman, Bell, & Bunney, 2012). Although social support is integral to the coaching process (Coussens et al, 2015), based on the results obtained, we can assume that athletes' prosocial behaviors are not dependable of the Perceived social support provided by the coaches. However, future investigations should address if some specific dimension of social support (emotional, esteem, informational, and tangible) may promote and potentiate cooperation within competitive teams.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that coaching competency is associated with athletes’ satisfaction with their coaches, 5 , 6 self-perceived antisocial behaviors, 7 perceptions of role ambiguity, 8 and perceptions of coach support. 9 These empirical findings imply that coaching competency serves as a means to predict many important athlete behavioral and attitudinal outcomes.…”
Section: Introductionmentioning
confidence: 99%